1999
DOI: 10.1029/1998pa900021
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse spectral reflectance as a proxy for percent carbonate content in North Atlantic sediments

Abstract: Abstract. Diffuse reflectance records from Feni Drift in the North Atlantic faithfully record sediment percent carbonate. A high-resolution, reflectance-based age model for these sediments derived from an orbitally tuned age model for western equatorial Atlantic, Ceara Rise sediments was generated by spectral frequency mapping. Power spectra of the Feni Drift record indicate statistically significant subMilankovitch cyclicity at 7.6-8.4 and 4.8-6.1 kyr. We infer that these -8 and-5 kyr cycles document a linkag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
66
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(73 citation statements)
references
References 43 publications
7
66
0
Order By: Relevance
“…This is in agreement with Ortiz et al (1999) who found subMilankovitch variability in the Atlantic Ocean for the period prior to the onset of the glacial cycles at ∼2.8 million years BP. However, this does not imply that ice sheets cannot change the characteristics of sub-Milankovitch variability.…”
Section: Summary and Discussionsupporting
confidence: 81%
“…This is in agreement with Ortiz et al (1999) who found subMilankovitch variability in the Atlantic Ocean for the period prior to the onset of the glacial cycles at ∼2.8 million years BP. However, this does not imply that ice sheets cannot change the characteristics of sub-Milankovitch variability.…”
Section: Summary and Discussionsupporting
confidence: 81%
“…2 and 3). Previous work has shown that DSR color spectra can be related to bulk sediment composition in many environments (Balsam and Deaton, 1991;Mix et al, 1999;Ortiz et al, 1999). For the Baja California record, a three-component R-mode factor model of the first-derivative transform of the percent reflectance spectra accounts for Ͼ93% of the data variance.…”
Section: Resultsmentioning
confidence: 99%
“…Proposed mechanisms are those including changes in the equatorial wind system equivalent to long-term changes in El Niño-Southern Oscillation (ENSO) and changes in the intensity of the Inter Tropical Convergence Zone (ITCZ) and monsoon variability (Stott et al, 2002). Moreover, older records show that high-frequency variability is a significant component of high-latitude and low-latitude climate prior to the onset of Northern Hemisphere glaciations (Ortiz et al, 1999;Steenbrink et al, 2003). Although the interpretation of these records is not straightforward they strengthen the idea that high-frequency components are persistent in the EarthTs climate and independent from the large ice sheets of the Late Pleistocene.…”
Section: Introductionmentioning
confidence: 99%
“…While it has been demonstrated that variations in the Earth's climate system at Milankovitch timescales (20 to 400-kyr) are caused by variations in the solar insolation and, hence, are orbitally induced, the origin of climate variability at subMilankovitch timescales (periods b 20-kyr) is still under debate. Possible forcing mechanisms that have been proposed for these high-frequency climate variations include non-linear response to harmonics or combination tones of the main orbital cycles (Pestiaux et al, 1988;Hagelberg et al, 1994;Ortiz et al, 1999), twice-yearly overhead passage of the sun across the equator (Short and Mengel, 1986;Short et al, 1991), variation in solar output (Van Geel et al, 1999;Perry and Hsu, 2000;Bond et al, 2001) or periodic motion of the Earth and Moon (Keeling and Whorf, 2000).…”
Section: Introductionmentioning
confidence: 99%